High Dose Steroid Therapy to Prevent Severe Hypoxia in COVID-19 Patients: A Potential Solution for Low Resource Clinical Setting - Edara, Lokesh (Cureus, 2020)
Coronavirus disease 2019 (COVID-19) can lead to severe respiratory failure; about 5%-10% of patients progress to severe pneumonia and respiratory distress, leading to multi-system failure. Dexamethasone helped to prevent mortality in COVID-19 patients. Low resource population in developing countries has limited access to critical care, but they do have access to oral and IV corticosteroids, anti-hyperglycemic agents, and anticoagulants. We report two patients with severe COVID-19 successfully treated with a high dose of methylprednisolone therapy. Early intervention with high dose corticosteroids in COVID-19 patients could be a solution for pacifying cytokine storms and reducing morbidity and mortality.